PERANCANGAN PUSAT KEBUGARAN DAN HEALTHY CAFE DI BANJARBARU - Nanda Azhari Kurnia; Nurfansyah Nurfansyah (UNIVERSITAS LAMBUNG MANGKURAT, 2026)
The design of the Fitness Center and Healthy Café in Banjarbaru aims to accommodate a healthy lifestyle for the community through the integration of sports activities and healthy food consumption in one area. This design uses an Active Design approach that focuses on increasing daily physical activity through spatial arrangement, circulation, and architectural elements that stimulate the natural movement of users. The design of the area was developed into a comfortable and inclusive active space, with the use of natural materials such as wood, exposed concrete, and vegetation to create a healthy and harmonious atmosphere. The design results are expected to be a forum that encourages the Banjarbaru community to live more actively, healthily, and sustainably.